Screenwriting Creative Labor and Professional Practice - Conor, Bridget (Taylor & Francis, 2014)
Screenwriting: Creative Labor and Professional Practice analyses the histories, practices, identities and subject which form and shape the daily working lives of screenwriters. Author Bridget Conor considers the ways in which contemporary screenwriters navigates and make sense of the labor markets in which they are immersed. Chapters explore areas including screenwriting as creative labor, screenwriters' working lives, the how-to genre, screenwriting inequalities, and myths of the profession.